Pengaruh Ekstrak Daun Kemangi (Ocimum santum L.) Terhadap pH Ikan Kembung - MHD. Fauzi Nasution; Kiki Nurtjahja; Rahmiati Rahmiati (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
Basil leaves contain secondary metabolites such as tannins, saponins, flavonoids and essential oils which have potential as antimicrobials. The aim of this study was to determine the ability of basil leaf extract as a natural preservative for mackerel. The study was conducted in vitro by observing the pH characteristics of mackerel treated with basil extract soaking for 4 and 8 hours with various concentrations of 0, 25, 50, 75 and 100%. The results showed that the physical quality of the samples during 4 hours of storage had the highest pH value at a concentration of 25%, namely pH 6.41, while at 8 hours of storage, the highest pH value was at a concentration of 100%, namely pH 7.47. The conclusion of the change in pH after soaking with the extract is included in the neutral category.